Relação entre desempenho tático, indicadores de crescimento e capacidades funcionais em jovens futebolistas - Borges, Paulo Henrique (2016)
The young football players during the early stages of sports training are characterized by having a large body variability due to different rates of growth and maturation. The influence of somatic maturity on the tactical performance of young players still needs further scientific research. In this sense, the objectives of this study were a) to compare the tactical performance, anthropometric indicators and functional capabilities between different maturational groups of young footballers; b) verify the relationship between the tactical performance, somatic maturity and functional abilities in young football players. To do so, they were recruited 48 soccer players (14.80 ± 1.52 years) belonging to an extension project of the State University of Maringa. Anthropometric measurements of weight, height, trunk-cephalic height and triceps skinfold and mid calf were held. The mature somatic was evaluated by equation proposed by Mirwald et al. (2002) that evaluates the age of growth speed peak. For the evaluation of functional abilities were performed tests of sit-and-reach, Yo-Yo Intermittent Recovery Test Level 1, handgrip test, modified abdominal and test vertical jumps Counter Movement Jump and Squat Jump. The tactical performance was achieved through the Tactical Assessment in Soccer System (FUT-SAT). Statistical analysis consisted of the Shapiro-Wilk test to verify the normality of the data, set by logarithmic equation for nonparametric data, Levene test to check the homogeneity of variances followed by Anova one-way test and post-hoc Bonferroni for comparison between groups. The Pearson correlation coefficient was used to determine the relationship between the following variables tactics, anthropometric and functional. Multiple linear regression analysis was used to estimate the relative contributions of anthropometric, physical performance and somatic maturity in the range of tactical football performance indicators. The results of Article 1 revealed that the advance in maturational classification reflected in higher anthropometric and functional values, but has low influence on the management of the game space. Already in Article 2, The results showed weak associations between the tactical performance of indexes, somatic maturity, functional abilities and anthropometric variables. It is concluded that the level of maturity does not associate to the tactical performance of young soccer players. Thus, clubs must select young players not only based on the physical and morphological performance, but also in the tactical and technical qualities.